Notions of nationalism - Periwal, Sukumar (Central European University Press ; Oxford University Press [distributor], 1995)
In recent years, following the end of the cold war and the relative simplicities of the bipolar confrontation, nationalism has re-emerged as a dominant force and ideology in our world. Everywhere, peoples who had been confined within the borders of countries with which they did not identify, and whose regimes they intensely disliked, have been seeking self-determination and democracy. Notions of Nationalism, as the title implies, is an open-minded exploration of a phenomenon that all of us need to understand.